Dampierella and Goodeniaphila: two new genera and three new species of Halticini from Australia, with a species key to the Halticini of Australia (Hemiptera: Heteroptera: Miridae: Orthotylinae) - Tatarnic, Nikolai J. (Zootaxa, 2009)
Two new genera of Halticini (Heteroptera: Miridae) from Australia, Dampierella and Goodeniaphila, are described, and include the new species Dampierella schwartzi, Goodeniaphila cassis, and G. schuhi. Habitus photos, scanning electron micrographs and illustrations of salient characters, including the male and female genitalia, distribution maps, and host plant data are included. Additionally, a key to the Australian Halticini is given.